Morphological characterization of some species of aphids belonging to the Aphididae family on some ornamental plants in Karbala Governorate - Dheyaa Z. H AI-Hussein; Taha M. M Al-Sweedi (Journal of Kerbala for Agricultural Sciences, 2024)
Given the importance of the aphid, its many species, the multiplicity of its families, and its rapid spread on ornamental plants in the Holy Governorate of Karbala City Iraq, this study was conducted and it aimed to diagnose some of the most important types of aphids belonging to the Aphididae family on ornamental plants in the Karbala Governorate. of the Aphididae family on ornamental plants in Karbala Governorate by selecting a group of nurseries distributed over six areas of the governorate, which comprised (the city center, Imam Aoun area, Al-Husseiniyah area, Al-Boubiyat area, Al-Har area and Al-Hindiya area). This study was conducted during the year 2023-2024 AD in one of the laboratories of the Plant Protection Department - College of Agriculture - University of Karbala. this study showed the presence of a large group of aphid colonies on ornamental plants, including the fine plum aphid (Hyalopterus pruni). This species was found on the Ruilia bretoniana plant. It is registered in Iraq The oat or bird cherry aphid (Rhopalosiphum padi) was found on the Damascus rose plant and was not recorded in Iraq. The black citrus or camellia aphid (Toxoptera auranti) was found on the African rose plant and was not recorded in Iraq. The hawthorn aphid (Dysaphis crataegi) was found on the Sanchezia plant. It is registered in Iraq ornamental plants in most nurseries.